(untitled) (Italian Journal of Public Health, 2006)
Medicines have important effect on population health and it is important to have a system for assessing their effects and monitoring their use, expenditure and price. The basis for all these objectives is the availability of an internationally valid classification system of medicines and a measurement system of their utilisation. Since 1996 the WHO Headquarter has adopted and proposed the ATC (Anatomical Therapeutical Chemical) classiifcation and the DDD (Defined Daily Dose) as the global standard for medicine classification and utilisation sudies, respectively. The EURO-MED-STAT project has defined the criteria for the production, validation and maintenance of national registers with validated ATC codes and DDD values, as suggested by WHO. A register with a valid ATC code and DDD value is able to provide reliable information allowing calculation of utilisation and expenditure indicators (Utilisation in DDD; DDD/1000inh/day and Expenditure per DDD).